EMPLOYEE FLOURISHING, ISLAMIC HUMAN CAPITAL, AND EMPLOYEE PERFORMANCE: THE MEDIATING ROLE OF INNOVATIVE WORK BEHAVIOUR - Aris Octavianto; Anang Kistyanto; Dewie Tri Wijayati Wardoyo (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study examines the effects of employee flourishing and Islamic human capital on employee performance, with innovative work behavior as a mediating variable. A quantitative approach was employed using a survey method involving 246 employees of Toserba Sunan Drajat across East Java. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that employee flourishing and Islamic human capital have positive and significant effects on employee performance and innovative work behavior. Innovative work behavior also shows a positive and significant effect on employee performance. Furthermore, innovative work behavior significantly mediates the relationship between employee flourishing and employee performance, as well as between Islamic human capital and employee performance. This study contributes to human resource management literature by clarifying the behavioral mechanisms linking employee flourishing and value-based human capital to performance in a competitive retail context.